The role of worker flows in the dynamics and distribution of UK unemployment - Michael W. L. Elsby; Jennifer C. Smith; Jonathan Wadsworth (Institute for the Study of Labor (IZA), 2011)
Unemployment varies substantially over time and across subgroups of the labour market. Worker flows among labour market states act as key determinants of this. We examine how the structure of unemployment across groups and its cyclical movements across time are shaped by changes in labour market flows. Using novel estimates of flow transition rates for the UK over the last 35 years, we decompose unemployment variation into parts accounted for by changes in rates of job loss, job finding and flows via non-participation. Close to two-thirds of the volatility of unemployment in the UK over this period can be traced to rises in rates of job loss that accompany recessions. The share of this inflow contribution has been broadly the same in each of the past three recessions. Decreased job-finding rates account for around one-quarter of unemployment cyclicality and the remaining variation can be attributed to flows via non-participation. Digging deeper into the structure of unemployment by gender, age and education, the flow-approach is shown to provide a richer understanding of the unemployment experiences across population subgroups.
urn:nbn:de:101:1-20110621445
Keywords: E24; J6; 330; labour market; unemployment; worker flows